Problem solving and comprehension - Whimbey, Arthur (Routledge, 2010)
This popular book shows students how to increase their power to analyze problems and to comprehend what they read. First, it outlines and illustrates the method that good problem solvers use in attacking complex ideas. Then, it provides practice in applying these methods to a variety of comprehension and reasoning questions. Books on the improvement of thinking processes have tended to be complicated and less than useful, but the authors of this renowned text emphasize a simple but effective approach. The ""Whimbey Method"" of teaching problem solving is now recognized as an invaluable means o.